Microscope ⁃ assisted transoral ⁃transpharyngeal reduction and fixation of basilar invagination and atlantoaxial dislocation - Wei⁃jie ZHU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2012)
Objective To study the outcome of the transoral reduction and fixation of basilar invagination and atlantoaxial dislocation, to evaluate this novel technique involving a microscope⁃assisted anterior release and reduction and fixation through a transoral⁃transpharyngeal approach and describe the safety and efficacy of a new minimal invasive technique for the irreducible atlantoaxial dislocation (IADD). Methods A prospective clinical study was performed. Three consecutive irreducible atlantoaxial dislocation patients underwent a microscope ⁃ assisted anterior release and reduction and fixation through transoral⁃transpharyngeal approach. Transoral atlantoaxial reduction plate (TARP) for anterior fixation and autologous morselized bone grafting were used during the operation. The Japanese Orthopaedic Association (JOA) scoring system was used to evaluate each patient's neurological status pre⁃ and post⁃operatively, and serial MRI and radiographs were used to evaluate the status of the reduction including the atlantoaxial interval and cervicomedullary angle were also measured. The clinical features, imaging data, special preoperative preparation, surgical approach, skills and postoperative complications of the 3 cases were analyzed. Results The average operation time was 130 min (110 min, 130 min, 150 min, respectively) and the mean estimated blood loss was 150 ml (100 ml, 200 ml, 150 ml, respectively). According to the postoperative CT all the 3 plates and 12 screws were appropriately placed and fixed. All cases of basilar invagination and atlantoaxial dislocation were corrected differentially in terms of anatomic reduction and neurological disturbances were reversed remarkably. The improvement rate of spinal cord function was 75.00%, 40.00%, 56.25%, respectively according to JOA score, average improvement rate was 57.08%, and average recovery rating was "good". Postoperative nosocomial intracranial infection occurred in one case and was cured finally. Conclusion Microscope⁃assisted transoral⁃transpharyngeal reduction and fixation for the treatment of basilar invagination and atlantoaxial dislocation is feasible and valuable.